Banjarmasin City's Readiness Strategy to Become a Fishery Buffer - Ellyn Normelani; Rizki Perdana Salan; Aida Rahmawaty; Galuh Bayuaji; Ariane Mariati; Annisa Mursyidah; Miftahani Zakiati; Emmy Maulida (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
This research aims to obtain strategies for increasing regional capacity, potential, and investment expansion; obtain strategies for strengthening the IKN buffer function; obtain strategies for strengthening collaboration/cooperation between IKN buffer regions, provinces, and the center; and compile an action plan for the readiness of Banjarmasin City as a buffer for IKN. The research method that is used in this study is a quantitative descriptive analysis method using the SWOT analysis technique to describe and analyze the readiness of Banjarmasin City to become a buffer for the IKN. The analysis shows that Banjarmasin City's position as a buffer zone for the new capital city (IKN) is strong enough to face significant challenges to its development. The recommended strategy is 'diversification,' meaning that Banjarmasin City, as a buffer zone for the new capital city (IKN), is in an ideal situation but faces difficulties in continuing to grow if it relies solely on existing strategies. Based on the analysis, it is recommended that Banjarmasin City maximize its role by choosing to act as both a buffer zone and a sub-buffer zone for the new capital city, supported by an aggressive strategy to maximize the utilization of available opportunities.